POSS (Polyhedral Oligomeric Silsesquioxane) resin solution with high light transmittance, composite coating and preparation method of POSS resin solution
A high-transmittance POSS composite coating was prepared by using a composite solution of POSS transparent resin, AR, and unsaturated polyester resin. This solved the problems of insufficient purity and compositeness of POSS coatings in the prior art, achieving high transmittance and excellent mechanical properties, making it suitable for display screen protection.
Patent Information
- Application Number
- CN202511304168.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-12
- Publication Date
- 2025-12-16
AI Technical Summary
The synthesis of existing POSS-based coatings suffers from numerous by-products, complex processes, high costs, and insufficient research on composite systems with other optical coating materials, resulting in poor light transmittance and performance, which limits their application in high-end display devices.
A high-transmittance POSS composite coating was prepared by using a composite solution of POSS transparent resin, AR and unsaturated polyester resin, and low-temperature baking and UV curing. The POSS resin solution was formed by the hydrolysis and condensation reaction of methylcyclotetrasiloxane, allylsilane coupling agent and tetraethylammonium hydroxide, and then mixed with AR and unsaturated polyester resin and coated and cured on the substrate.
The POSS composite coating achieves a light transmittance of >92% and a low haze of <0.8%, possessing excellent pencil hardness, scratch and abrasion resistance, adhesion, and impact resistance, making it suitable for surface protection of LCD or OLED displays.
Smart Images

Figure CN121136099A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of coating materials, in particular to a POSS resin solution with high light transmittance, a composite coating and a preparation method thereof. BACKGROUND
[0002] As a key carrier for presenting video and image information, the stability and durability of the external protective structure of the display screen directly affect the overall performance and service life of the equipment. At present, the outermost layer of the mainstream display screen is mostly made of glass cover plate as the substrate, and a functional coating is often added on the surface to improve its anti-scratching, wear resistance and impact resistance and other properties. Among them, polyhedral oligomeric silsesquioxane (POSS) coating is widely used in display screen surface coating materials due to its excellent mechanical strength and optical transparency. In order to balance the visual display effect and surface performance, it is particularly important to develop a POSS composite coating with high light transmittance.
[0003] POSS resin can be generally synthesized by hydrolysis and condensation method or functional group derivation method, and its general molecular formula is (RSiO3 / 2) n wherein R represents an organic functional group connected to each silicon atom, and n is generally between 6 and 12, forming a cage-shaped or partially cage-shaped siloxane core structure. The light transmittance of the material is closely related to its chemical structure, ordered arrangement of molecular chains, types of additives used and preparation process parameters. The inner core of the POSS molecule is a regular silicon-oxygen cage framework, which has uniform dispersion characteristics at the nanoscale, can significantly reduce the scattering loss in the visible light region, and thus helps to achieve high light transmittance.
[0004] However, there are still some obvious bottlenecks in the preparation and technical application of existing POSS-based coatings:
[0005] (1) During the synthesis of POSS resin, a large number of by-products (such as linear siloxane or cyclic silane, etc.) are often accompanied, resulting in low purity of the final sample. These impurities can cause the optical uniformity of the coating to decrease, thereby affecting the light transmittance performance and weakening the anti-scratch and wear resistance;
[0006] (2) The existing synthesis path is usually complicated in steps, with many intermediates, and requires high control of reaction conditions (such as temperature, catalyst, solvent, etc.), which causes the process complexity and production cost to rise, and at the same time restricts the consistency and yield of the product;
[0007] (3) Although the POSS resin itself has excellent performance, the composite system of the POSS resin and other optical coating materials such as anti-reflection (AR) solution, other transparent resins, etc. is not fully studied. The systematic study on the matching, interface compatibility, coating firmness and long-term environmental stability of the composite coating of POSS and AR and other transparent resins is still insufficient, which limits the large-scale application of the composite coating in high-end display devices. SUMMARY
[0008] The purpose of the present application is to provide a high-transmittance POSS composite coating composed of a POSS transparent resin and an AR (anti-reflection) and unsaturated polyester resin composite solution coated on a substrate, with a transmittance > 92% and good pencil hardness, scratch resistance, wear resistance, adhesion, bending resistance, impact resistance and other properties. The POSS transparent hard coating has excellent transparency and hardness, can effectively protect the surface from scratching and wear, the unsaturated polyester resin has good transmittance, and the AR coating can reduce light reflection and improve transmittance.
[0009] Another purpose of the present application is to provide a preparation method of a high-transmittance POSS composite coating, which has a transmittance > 92% through low-temperature baking and UV curing, and has good pencil hardness, scratch resistance, wear resistance, adhesion, bending resistance, impact resistance and other properties.
[0010] The present application solves the technical problem by using the following technical scheme.
[0011] In one aspect, the present application provides a preparation method of a high-transmittance POSS resin solution, comprising the following steps:
[0012] S1, methylcyclosiloxane, allyl-containing silane coupling agent, deionized water, ethanol are mixed, stirred uniformly, then tetraethylammonium hydroxide is added dropwise, the pH is controlled to 9-11, the temperature is raised to 50℃, the hydrolysis reaction is carried out for 2-4h, then the temperature is raised to 80-100℃, the stirring rate is 500rpm / min, the condensation reaction is carried out for 8-10h under the condition of nitrogen protection atmosphere, and then rotary evaporation, washing, filtration and drying are carried out to obtain a POSS resin powder; wherein the allyl-containing silane coupling agent is preferably allyltrimethoxysilane;
[0013] S2, the POSS resin powder and acetonitrile are mixed, filtered, the solid after filtration is mixed with isopropyl alcohol and polyethylene glycol, and then static separation is carried out to obtain the POSS resin solution.
[0014] In some embodiments of the present application, in the step S1, the ratio of methylcyclotetrasiloxane, allyl-containing silane coupling agent and tetraethylammonium hydroxide is (40-50) g:(10-20) g:(1-5) mL.
[0015] In some embodiments of the present application, in the step S2, the volume ratio of isopropyl alcohol and polyethylene glycol is 3:1.
[0016] A POSS resin solution with high light transmittance is prepared by the above method.
[0017] In one aspect, the present application provides a method for preparing a POSS composite coating with high light transmittance, comprising the following steps: mixing AR solution, unsaturated polyester resin and the above-mentioned POSS resin solution at 300 r / min for 1 h, vacuum degassing to obtain a mixed solution; coating the mixed solution on a substrate, annealing at 50-60℃ for 3-5 min, UV curing to obtain a composite POSS coating material.
[0018] In some embodiments of the present application, the content of AR solution is 2-5% by weight of the total mixed solution, the content of unsaturated polyester resin is 10-15% by weight of the total mixed solution, and the rest is the POSS resin solution.
[0019] In some embodiments of the present application, the content of AR solution is 5% by weight of the total mixed solution, the content of unsaturated polyester resin is 10% by weight of the total mixed solution, and the rest is the POSS resin solution.
[0020] A POSS composite coating with high light transmittance is prepared by the above method.
[0021] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0022] The POSS resin solution and the high light transmittance POSS composite coating prepared therefrom provided by the present application are mainly prepared by coating and curing a composite solution of a POSS transparent resin and AR (anti-reflective) and unsaturated polyester resin on a substrate. The composite coating has a light transmittance >92%, a low haze <0.8%, and also has good pencil hardness, scratch resistance, wear resistance, adhesion, bending resistance, impact resistance and other properties. It is mainly used to protect the surface of a liquid crystal or OLED display screen while not affecting the light transmittance. The POSS transparent hard coating has excellent transparency and hardness, which can effectively protect the surface from scratches and wear, the unsaturated polyester resin has good light transmittance, and the AR coating can reduce light reflection and improve light transmittance. BRIEF DESCRIPTION OF DRAWINGS
[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 This is a schematic diagram of the process of the POSS composite coating in Embodiment 1 of the present invention;
[0025] Figure 2 The Fourier transform infrared spectrum of the POSS resin solution in Example 1 of this invention;
[0026] Figure 3 The image shows the Fourier transform infrared spectrum of the POSS composite coating in Example 1 of this invention. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0028] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other. The present invention will now be described in detail with reference to specific embodiments.
[0029] On one hand, embodiments of the present invention provide a method for preparing a POSS resin solution with high light transmittance, see... Figure 1 This includes the following steps:
[0030] S1. Methylcyclotetrasiloxane (Dow Corning PMX-0244), allyltrimethoxysilane (Zhengzhou Gaike Technology 2551-83-9), deionized water, and ethanol are mixed and stirred evenly. Then, tetraethylammonium hydroxide (Kent Catalytic Materials Co., Ltd. 77-98-5) is added dropwise, and the pH is controlled at 9-11. The temperature is raised to 50°C, and the hydrolysis reaction is carried out for 2-4 hours. Then, the temperature is raised to 80-100°C, and the stirring rate is 500 rpm / min. The condensation reaction is carried out under a nitrogen protective atmosphere for 8-10 hours. The mixture is then rotary evaporated. After washing, filtering, and drying, POSS resin powder is obtained.
[0031] S2, mix POSS resin powder and acetonitrile, filter, mix the filtered solid with isopropanol (Jinzhou Petrochemical, 99.9% purity) and polyethylene glycol (Jinzhou Petrochemical, 99.9% purity), let stand and separate to obtain the POSS resin solution.
[0032] In some embodiments of the present invention, in step S1, the ratio of methylcyclotetrasiloxane, allyltrimethoxysilane and tetraethylammonium hydroxide is (40-50)g:(10-20)g:(1-5)mL.
[0033] In some embodiments of the present invention, in step S2, the volume ratio of isopropanol to polyethylene glycol is 3:1.
[0034] A method for preparing a high-transmittance POSS composite coating includes the following steps: mixing and stirring an AR solution (Shanghai Juanrou New Technology, JR-AR-965), an unsaturated polyester resin (Lianrui 2126-AP), and the POSS resin solution according to any one of claims 1-3 at 300 r / min for 1 h, followed by vacuum degassing to obtain a mixed solution; coating the mixed solution onto a substrate, baking at 50-60℃ for 3-5 min for heat annealing, and UV curing to obtain a composite POSS coating material.
[0035] AR solution (anti-reflective solution) forms an AR coating after being applied to a substrate. It is an optical thin film that increases light transmittance by reducing light reflection from optical surfaces. It is mainly composed of nanoscale thin films of silicon dioxide and other materials with different refractive indices (TiO2, MgF2) stacked together.
[0036] In some embodiments of the present invention, the AR solution content is 2-5% and the unsaturated polyester resin content is 10-15% by weight of the total mass of the mixed solution, with the remainder being POSS resin solution. More preferably, the AR solution content is 5%, the unsaturated polyester resin content is 10%, and the remainder is POSS resin solution.
[0037] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0038] Example 1
[0039] Preparation: 45g of methylcyclotetrasiloxane, 15g of allyltrimethoxysilane, 250mL of deionized water, and 250mL of ethanol were added sequentially to the reaction vessel. After stirring evenly, 3mL of tetraethylammonium hydroxide was slowly added dropwise. The pH was measured to be 10. The temperature was raised to 50℃ and the hydrolysis reaction was carried out for 3 hours. Then, the temperature was raised to 90℃ and the stirring rate was 500rpm / min. The condensation reaction was carried out for 9 hours under a nitrogen protective atmosphere. Then, excess solvent was removed by rotary evaporation. After washing with deionized water and isopropanol and filtering, the sample was freeze-dried to obtain a white powder sample of POSS resin.
[0040] Purification: Mix 50g of POSS resin powder with 80mL of acetonitrile and filter. Transfer the filtered solid to a separatory funnel, add 60mL of isopropanol and 20mL of polyethylene glycol (Jinzhou Petrochemical, 99.9% purity), shake for 2min to mix evenly, let stand and separate, collect the purified product POSS resin solution, and test the pH = 7.
[0041] Composite coating: 5% AR solution, 10% unsaturated polyester resin (Lianrui 2126-AP) and POSS resin solution by mass ratio were mixed and stirred at 300 r / min for 1 h, vacuum degassing treatment was performed, and then the mixture was coated on a PET substrate. After heat annealing at 60℃ for 3 min, UV curing was performed, and then the coating was repeated on the other side to obtain the composite POSS coating material.
[0042] Fourier transform infrared spectroscopy analysis of the POSS resin solution yielded the following results: Figure 2 As shown. Infrared spectroscopy tests were mainly performed using a Fourier transform infrared spectrometer (FT-IR) according to the GB / T6040-2019 standard. Solid samples were tested using the KBr pellet method, and liquid samples were tested using a solvent of isopropanol and polyethylene glycol in a 3:1 ratio as a blank.
[0043] from Figure 2 As can be seen from this, the main peak is 1100cm. -1 The antisymmetric stretching vibration of Si-O-Si at the 950 cm⁻¹ is a characteristic peak of siloxane compounds. For cage-like POSS structures, due to the high symmetry and rigidity of the Si-O-Si bond, this peak often appears as a strong and sharp absorption peak, which is a core feature of the POSS skeleton, indicating that the product has a typical siloxane cage structure. The presence of multiple Si-CH₃ peaks confirms the presence of methyl substituents in the POSS molecule, and that the number and symmetry of the substituents affect the peak shape. Furthermore, the peak shape is observed at 950 cm⁻¹. -1 The peak at 1710 cm⁻¹ is a characteristic peak of the Si-OH bond. -1 The peak at 2900 cm⁻¹ is a characteristic peak of the allyl double bond. -1 The nearby peaks are characteristic of CH bonds.
[0044] Fourier transform infrared spectroscopy analysis was performed on the composite POSS coating material, and the results are as follows: Figure 3 As shown. It can be seen that, unlike the POSS resin solution, except for being located at 1100 cm... -1 In addition to the characteristic main peak of Si-O-Si, the Si-CH3 peak, and the Si-OH bond characteristic peak, there are also obvious C=O and C=C characteristic peaks. Double bond peaks are generally not present in pure POSS. Therefore, the C=O and C=C characteristic peaks belong to unsaturated polyester resin and AR solution (prepared by reacting styrene-acrylate emulsion, alkoxysilane, metal salt, various additives and solvents).
[0045] Example 2
[0046] In Example 1, methylcyclotetrasiloxane was replaced with 40g, allyltrimethoxysilane with 10g, deionized water and ethanol with 200mL, tetraethylammonium hydroxide with 1mL, the hydrolysis reaction time was changed to 2h, the condensation reaction temperature was changed to 80℃, the time was changed to 8h, and other conditions remained unchanged, resulting in white powder products POSS resin, POSS resin solution and composite POSS coating material.
[0047] Example 3
[0048] In Example 1, methylcyclotetrasiloxane was replaced with 50g, allyltrimethoxysilane with 20g, deionized water and ethanol with 300mL, tetraethylammonium hydroxide with 5mL, the hydrolysis reaction time was changed to 4h, the condensation reaction temperature was changed to 100℃, and the time was changed to 10h, while other conditions remained unchanged, to obtain white powder products POSS resin, POSS resin solution and composite POSS coating material.
[0049] Comparative Example 1
[0050] The white powder product POSS resin obtained in Example 1 was not purified. It was dissolved in isopropanol and coated onto a PET substrate with 5% AR solution and 10% unsaturated polyester resin by the same process to obtain a composite POSS coating material. Various properties were then tested.
[0051] Comparative Example 2
[0052] The POSS resin solution obtained in Example 1 was directly coated onto a PET substrate using the same process to obtain a POSS coating treatment. No AR solution or unsaturated polyester resin was used, and various properties were tested.
[0053] Comparative Example 3
[0054] The POSS resin solution obtained in Example 1 and 10% by mass of unsaturated polyester resin were directly coated onto a PET substrate using the same process to obtain a POSS coating treatment without AR solution, and various properties were tested.
[0055] Comparative Example 4
[0056] The POSS resin solution obtained in Example 1 and AR solution accounting for 5% of the total mass were directly coated on a PET substrate using the same process to obtain a POSS coating treatment without unsaturated polyester resin. Various properties were tested.
[0057] Comparative Example 5
[0058] Allyltrimethoxysilane was removed, and other conditions were the same as in Example 1 to obtain a composite POSS coating material, and its various properties were tested.
[0059] Comparative Example 6
[0060] Isopropanol was replaced with ethanol, and other conditions were the same as in Example 1, to obtain a composite POSS coating material, and its various properties were tested.
[0061] Comparative Example 7
[0062] UV curing was changed to 60℃ heat curing, and other conditions were the same as in Example 1 to obtain a composite POSS coating material, and various properties were tested.
[0063] Comparative Example 8
[0064] The heat annealing temperature was changed to 100℃, and other conditions were the same as in Example 1, to obtain a composite POSS coating material, and various properties were tested.
[0065] Experimental Example
[0066] The performance of the composite POSS coating materials of Examples 1-3 and Comparative Examples 1-8 was tested, and the results are shown in Table 1.
[0067] The thickness of the substrate and coating was tested using a micrometer according to ASTM D3652 standard. Light transmittance and haze were tested using a spectrophotometer according to ASTM D1003 and GB / T2410-2008 standards, employing a d / 0 measurement structure. Surface hardness was tested using pencil hardness according to ASTM D3363 standard, and rubber abrasion resistance (1000 cycles) was tested according to GB10006-1988 standard. Adhesion was tested using the cross-cut adhesion test (0B, 1B, 2B, 3B, 4B, 5B) according to GB / T9286-2021 standard, and water droplet angle testing was conducted using a water droplet angle tester according to GB / T30447-2013 standard.
[0068] Table 1
[0069] Performance Thickness (pm) Transmittance Haze Pencil hardness Eraser resistance Adhesion Water drop angle Example 1 25 96% 0.81 B Pass 5B 110° Example 2 24 95% 0.88 HB Pass 5B 108° Example 3 26 93% 0.97 B Pass 4B 102° Comparative Example 1 25 85% 3.45 B Pass 4B 99° Comparative Example 2 23 88% 2.42 HB Pass 4B 105° Comparative Example 3 24 90% 1.96 HB Pass 4B 103° Comparative Example 4 24 91% 1.65 HB Pass 4B 104° Comparative Example 5 23 90% 1.83 HB Pass 4B 95° Comparative Example 6 25 89% 2.21 HB Pass 4B 102° Comparative Example 7 24 82% 5.82 B Pass 3B 99° Comparative Example 8 27 80% 7.21 2B Pass 2B 100°
[0070] Table 1 shows that the treatment conditions have little effect on eraser resistance and water droplet angle. Increasing or decreasing the proportion of raw materials leads to incomplete reaction, slightly reducing transmittance, but has little impact on other properties. POSS coatings without purification treatment have more impurities, significantly reducing transmittance and increasing haze. POSS coatings without AR solution have slightly reduced transmittance, but other properties are not significantly affected because the nanomaterials with different refractive indices in the AR coating can reduce reflected light from optical surfaces, thereby increasing transmittance. POSS coatings without unsaturated polyester resin have slightly reduced transmittance, but other properties are not significantly affected because blending POSS with transparent resin (such as unsaturated polyester resin) allows for high transmittance through nanoscale dispersion. Removing allyltrimethoxysilane reduces transmittance and water droplet angle because the allyl group can react with Si-O-Si to form a Si-CH3 cross-linked network, reducing light reflection loss, and forming hydrophobic Si-OH groups during hydrolysis, reducing surface contamination. Replacing isopropanol with ethanol leads to a decrease in light transmittance because ethanol evaporates more quickly, causing POSS molecules to aggregate. Isopropanol can regulate the phase separation of POSS molecular chains and improve dispersibility. Changing UV curing to 60℃ heat curing results in a significant decrease in light transmittance and adhesion because the UV curing process can quickly crosslink to form a dense network, reducing microscopic defects. Changing the heat annealing temperature to 100℃ also results in a significant decrease in light transmittance and adhesion, and an increase in pencil hardness. This is because excessively high heat annealing temperatures (>80℃) cause POSS chain rearrangement, leading to a significant decrease in light transmittance.
[0071] In summary, the POSS resin solution and the high-transmittance POSS composite coating made from the POSS resin solution provided by this invention are mainly formed by coating and curing a composite solution of POSS transparent resin, AR (anti-reflective) resin, and unsaturated polyester resin on a substrate. The composite coating has a transmittance >92%, a low haze <0.8%, and also possesses good pencil hardness, scratch and wear resistance, adhesion, bending resistance, and impact resistance. It is mainly used to achieve surface protection for liquid crystal or OLED displays without affecting the transmittance. Among them, the POSS transparent hard coating has excellent transparency and hardness, which can effectively protect the surface from scratches and wear, while the AR coating can reduce light reflection and improve transmittance.
[0072] The embodiments described above are some, but not all, embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A method for preparing a high-transmittance POSS resin solution, characterized in that, Includes the following steps: S1. Methylcyclotetrasiloxane, allyl-containing silane coupling agent, deionized water, and ethanol are mixed and stirred until homogeneous. Tetraethylammonium hydroxide is added dropwise, and the pH is controlled at 9-11. The temperature is raised to 50°C, and the hydrolysis reaction is carried out for 2-4 hours. Then, the temperature is raised to 80-100°C, and the stirring rate is 500 rpm / min. The condensation reaction is carried out under a nitrogen protective atmosphere for 8-10 hours. The product is then rotary evaporated, washed, filtered, and dried to obtain POSS resin powder. S2, mix POSS resin powder and acetonitrile evenly, filter, mix the filtered solid with isopropanol and polyethylene glycol, let stand and separate the liquids to obtain the POSS resin solution.
2. The method for preparing a high-transmittance POSS resin solution according to claim 1, characterized in that, In step S1, the ratio of methylcyclotetrasiloxane, allyl-containing silane coupling agent and tetraethylammonium hydroxide is (40-50)g:(10-20)g:(1-5)mL.
3. The method for preparing a high-transmittance POSS resin solution according to claim 1, characterized in that, In step S2, the volume ratio of isopropanol to polyethylene glycol is 3:
1.
4. A high-transmittance POSS resin solution, characterized in that, It is prepared by the method described in any one of claims 1-3.
5. A method for preparing a high-transmittance POSS composite coating, characterized in that, The process includes the following steps: mixing and stirring AR solution, unsaturated polyester resin and POSS resin solution according to any one of claims 1-3 at 300 r / min for 1 h, degassing under vacuum to obtain a mixed solution; coating the mixed solution onto a substrate, baking at 50-60℃ for 3-5 min for heat annealing, and UV curing to obtain a composite POSS coating material.
6. The method for preparing the high-transmittance POSS composite coating according to claim 5, characterized in that, The AR solution comprises 2-5% of the total mass of the mixed solution, the unsaturated polyester resin comprises 10-15%, and the remainder is POSS resin solution.
7. The method for preparing the high-transmittance POSS composite coating according to claim 5, characterized in that, The AR solution comprises 5% of the total mass of the mixed solution, the unsaturated polyester resin comprises 10%, and the remainder is POSS resin solution.
8. A high-transmittance POSS composite coating, characterized in that, It is prepared by the method described in any one of claims 5-7.
Citation Information
Patent Citations
Photocurable acrylic coating compositions having good adhesion properties to a subsequent coating and corresponding coated substrates
CN102056993A
POSS (Polyhedral Oligomeric Silsesquioxane) synthetic resin and preparation method thereof, POSS coating composition as well as preparation method and application thereof
CN117229508A
Anti-reflection film and preparation method and application thereof
CN120044643A